Post-oxidation of all-organic electrocatalysts to promote O−O coupling in water oxidation - Chun-Ting He; Li-Hong Yu; Haiming Liu; Qing Wang; Zi-Ming Ye; Jia Zhang; Li-Dong Wang; Mei-Qian He; Xue-Feng Zhang; Hong-Gang Du; Zi-Wei Lu; Jian Yang; et al. (Nature Communications)
Abstract Covalently bonded metal-free electrocatalysts exhibit significant potential for sustainable energy technologies, yet their performances remain unsatisfactory compared with metal-based catalysts. Herein, we propose an all-organic electrocatalyst, MEC-2, that conforms to the infrequent oxide path mechanism in alkaline oxygen evolution reaction through post-oxidation modification. MEC-2 achieves an intrinsic overpotential of 257.7 ± 0.6 mV at 10 mA·cm−2 and possesses durability with negligible degradation over 100,000 CV cycles or 250 h of operation at 1.0 A·cm−2, being comparable to the advanced metal-based OER electrocatalysts. The 18O-labeled operando characterization and theoretical calculations unveil that post-oxidation modification enhances the electron affinity to OH intermediates, and adjusts the adsorption configuration and proximity distance of O intermediates, thereby promoting direct O−O radical coupling. In this work, we show a fresh perspective for understanding the role of non-metallic elements/functional groups in electrocatalysis, and to a certain extent, narrows the gap between all-organic electrocatalysts and metal-based electrocatalysts.